Microstructure and thermoelectric properties of CrN and CrN/Cr2N thin films. (2nd August 2018) - Gharavi, M A; Kerdsongpanya, S; Schmidt, S; Eriksson, F; Nong, N V; Lu, J; Balke, B; Fournier, D; Belliard, L; le Febvrier, A; Pallier, C; Eklund, P
Abstract: CrN thin films with an N/Cr ratio of 95% were deposited by reactive magnetron sputtering onto (0 0 0 1) sapphire substrates. X-ray diffraction and pole figure texture analysis show CrN (1 1 1) epitaxial growth in a twin domain fashion. By changing the nitrogen versus argon gas flow mixture and the deposition temperature, thin films with different surface morphologies ranging from grainy rough textures to flat and smooth films were prepared. These parameters can also affect the CrN x system, with the film compound changing between semiconducting CrN and metallic Cr2 N through the regulation of the nitrogen content of the gas flow and the deposition temperature at a constant deposition pressure. Thermoelectric measurements (electrical resistivity and Seebeck coefficient), scanning electron microscopy, and transmission electron microscopy imaging confirm the changing electrical resistivity between 0.75 and 300, the changing Seebeck coefficient values between 140 and 230, and the differences in surface morphology and microstructure as higher temperatures result in lower electrical resistivity while gas flow mixtures with higher nitrogen content result in single phase cubic CrN.